Effect of low-intensity pulsed ultrasound on injured temporomandibular joints with or without articular disc removal in a rabbit model - Yuki Saito; Takamitsu Tsutsui; Akihiro Takayama; Akinori Moroi; Kunio Yoshizawa; Koichiro Ueki (Elsevier, 2021)
Background/purpose: Dynamic stimulation can induce bone and cartilage growth. The purpose of this study was to examine the effect of low-intensity pulsed ultrasound (LIPUS) on injured temporomandibular joints (TMJs) in a rabbit model. Materials and methods: Twenty-four female Japanese white rabbits (age: 12-16 weeks, weight: 2.0-2.5 kg) were equally divided into 4 groups. In two groups, discectomy was performed with (the LD group) and without (the D group) subsequent LIPUS treatment. In the other groups, a sham operation was performed with (the LC group) and without (the C group) subsequent LIPUS treatment. Two animals in each group were sacrificed at each time point (2, 4, and 8 weeks postoperatively). Mandibular measurements were made using three-dimensional computed tomography. We performed histological and immunohistochemical examination of the articular disc, and the cartilage layer and bone at the 30- and 60-degree sites in each condyle. Results: There were no statistically significant differences among the groups in terms of thickness of the disc or the fibrous articular zone, or the number of BMP-2 positive cells. In terms of mandibular length, there were differences among the groups after 4 (P = 0.0498) and 8 weeks (P = 0.0260). Specifically, there was a difference between the LC group and the C group after 4 weeks (P = 0.014) and 8 weeks (P = 0.029). Conclusions: This study suggests that LIPUS has little effect on cartilage after TMJ injury. It may promote bone growth in a normal TMJ, although discectomy seems to reduce this effect.